2010
DOI: 10.1053/j.gastro.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

TFF2 mRNA Transcript Expression Marks a Gland Progenitor Cell of the Gastric Oxyntic Mucosa

Abstract: Background and Aims Gastric stem cells are located in the isthmus of the gastric glands, and give rise to epithelial progenitors that undergo bipolar migration and differentiation into pit and oxyntic lineages. While gastric mucus neck cells, located below the isthmus, express trefoil factor family 2 (TFF2) protein, TFF2 mRNA transcripts are concentrated in cells above the neck region in normal corpus mucosa, suggesting that TFF2 transcription is a marker of gastric progenitor cells. Methods Using a BAC stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 35 publications
3
109
0
1
Order By: Relevance
“…Previously, it is only in the oxyntic mucosa of trefoil factor-2 (TFF2) mice that successful lineage tracing has demonstrated progenitor stem cells in animal models 26 . Furthermore it has also been reported that the murine small intestinal and colonic crypt base columnar cells (CBCs) expressing lgr5, are actively cycling and are able to regenerate the entire cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it is only in the oxyntic mucosa of trefoil factor-2 (TFF2) mice that successful lineage tracing has demonstrated progenitor stem cells in animal models 26 . Furthermore it has also been reported that the murine small intestinal and colonic crypt base columnar cells (CBCs) expressing lgr5, are actively cycling and are able to regenerate the entire cell population.…”
Section: Discussionmentioning
confidence: 99%
“…BAC recombination was performed using the CreTM-FrtNeoFrt or the EGFPcre-Frt-kanFrt (pIGCN21) cassette, as described previously (65). Briefly, the CreTMFrtNeoFrt cassette was ligated into a p451 plasmid before generating a probe containing a 40-bp sequence homologous to the BAC sequence directly upstream of the ATG in exon 2 (Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In the corpus, some studies suggested that Sox2 + cells may represent long-lived stem cells scatered throughout the isthmus and in the lower part of the gastric unit [9]. Trefoil factor family 2 (Tf2 + ) cells were also described as shortlived progenitors in the isthmus region of the corpus [10]. More recently, lineage tracing experiments have shown that diferentiated mature chief cells expressing the Troy marker at the base of the corpus gastric glands can generate entirely labeled gastric units over a period of several months in vivo and long-lived organoids in vitro [11].…”
Section: Discovery Of Gastric Stem Cells and Their Markersmentioning
confidence: 99%